Seeing Through the Façade of Anorexia: A Grounded Theory of Emotional Change Processes Associated With Recovery From Anorexia Nervosa - Drinkwater, Danielle; Holttum, Sue; Lavender, Tony; Startup, Helen; Oldershaw, Anna (Frontiers in Psychiatry, 2022)
Abstract Objectives: Difficulties in managing emotions have been implicated in the development and maintenance of anorexia nervosa (AN), and psychological treatment models seek to address this in putative targets of change. Yet the field of psychotherapy remains unclear and insufficiently evidenced about the process of change and how this is actually achieved, including in what steps and in what order within clinical treatment. This qualitative study sought to develop theory about the process of emotional change during recovery from anorexia. Methods: Semi-structured interviews were carried out with nine women currently engaged in psychological treatment for anorexia. Interviews included questions pertaining to participants’ experience of anorexia, emotions, and emotion management. A constructivist version of grounded theory was employed. Results: The analysis produced 10 major categories, comprising over 60 focused codes. Categories were clustered together into three super categories, reflecting 3 distinct but interrelated phases of participants’ journeys towards recovery. The phases were: (1) Coping in a world of uncertainty, (2) Seeing through the façade of anorexia, and (3) Recovery and growth. Whilst movement towards later positions often appeared to be contingent on earlier ones, the analysis suggests that this was not an entirely linear process and that participants moved between positions as they grappled with the process of change. Participants came to view behaviours associated with anorexia as emotion-management strategies that were not working and as a façade. As they moved towards recovery and growth, they became less confined by their need for safety, and to see emotions as meaningful and valuable. Becoming more connected to emotional experience and expression, coincided with positive shifts in their intra and interpersonal relationships. Conclusions: These findings support the recent shift towards emotion-focused models of anorexia. They also highlight an important focus in supporting individuals with AN to connect with, and be guided by, emotional experiences in their relationships with themselves and the world around them. This new grounded theory offers a putative process of change that could be utilized to guide intervention development.